Busting the Gender Binary: Activities for Teaching Transgender Issues in Management Education. (December 2020) - Schwartz, H. Michael; Bilimoria, Diana
There is a growing need to teach management students about the diverse gender identities they may face as managers and leaders in the workplace. Management educators are generally ill-equipped to teach transgender issues, even in diversity management courses. In this article, we provide two activities for supplementing education about transgender experiences in management education courses. The first is an experiential exercise that works best as an introduction to the transgender experience. The second activity, which can be used both in classroom or online learning environments, offers a series of mini case studies (with suggested discussion questions and teaching notes) to help inform and guide students through more advanced reflection and discussion about real-world scenarios involving transgender employees in the workplace. A supplemental set of slides is also available to help management educators better understand transgender issues.